2022
DOI: 10.1038/s41598-022-21600-x
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet printing of mechanochromic fluorenylidene-acridane

Abstract: In mechanochromic material research, a serious problem is that mechanical treatment cannot be applied to the materials because of their responsiveness to stimuli. Inkjet printing is a useful solution deposition method for electronics, but materials must be processed to be suitable for an inkjet printer. Fluorenylidene-acridane (FA) exhibits ground-state mechanochromism with visual color changes and responds not only to mechanical pressure but also to alcohol. Alcohol inhibits the color change induced by mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Additionally, by harnessing the control of mechanochromism, we have developed a mechanochromic resin and demonstrated its application in inkjet printing technology. 19 In this paper, we focus on the cellulose nanofiber (CNF), which has numerous hydroxyl groups. CNF is garnering research attention because it is a biomass material derived from dietary fiber, potentially contributing to a sustainable environment and a decarbonized society.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, by harnessing the control of mechanochromism, we have developed a mechanochromic resin and demonstrated its application in inkjet printing technology. 19 In this paper, we focus on the cellulose nanofiber (CNF), which has numerous hydroxyl groups. CNF is garnering research attention because it is a biomass material derived from dietary fiber, potentially contributing to a sustainable environment and a decarbonized society.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Theoretical calculations suggested that this phenomenon is related to the interplay between aggregation/disaggregation and changes in the molecular conformation. Additionally, by harnessing the control of mechanochromism, we have developed a mechanochromic resin and demonstrated its application in inkjet printing technology …”
Section: Introductionmentioning
confidence: 99%